2012
DOI: 10.1021/jf301166j
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase Catalyzed Cross-Linking of Sodium Caseinate Improves Oxidative Stability of Flaxseed Oil Emulsion

Abstract: Sodium caseinate was modified by transglutaminase catalyzed cross-linking reaction prior to the emulsification process in order to study the effect of cross-linking on the oxidative stability of protein stabilized emulsions. The extent of the cross-linking catalyzed by different dosages of transglutaminase was investigated by following the ammonia production during the reaction and using SDS-PAGE gel. O/W emulsions prepared with the cross-linked and non-cross-linked sodium caseinates were stored for 30 days un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…Highest Z-average in 5 % WPC emulsion suggested that there was insufficient amount of whey proteins to cover the oil droplets, which led to the droplets flocculation and thus increase in Z-average, similar to the observations reported by Wang et al (2010). Ma et al (2012) prepared flaxseed oil emulsion using cross-linked sodium caseinate and reported mean droplet diameter of 0.16 μm (160 nm) at zero day. Similarly, Kentish et al (2008) reported mean droplet size in the range of 135±5 nm when flaxseed oil emulsion was homogenized at very high pressure (100 MPa) in presence of tween 40 surfactant.…”
Section: Particle Size Distributionsupporting
confidence: 79%
See 1 more Smart Citation
“…Highest Z-average in 5 % WPC emulsion suggested that there was insufficient amount of whey proteins to cover the oil droplets, which led to the droplets flocculation and thus increase in Z-average, similar to the observations reported by Wang et al (2010). Ma et al (2012) prepared flaxseed oil emulsion using cross-linked sodium caseinate and reported mean droplet diameter of 0.16 μm (160 nm) at zero day. Similarly, Kentish et al (2008) reported mean droplet size in the range of 135±5 nm when flaxseed oil emulsion was homogenized at very high pressure (100 MPa) in presence of tween 40 surfactant.…”
Section: Particle Size Distributionsupporting
confidence: 79%
“…The high stability of emulsions containing higher WPC concentrations (7.5, 10 and 12.5 %) may also be attributed to their antioxidative properties and their ability to bind some pro-oxidant impurities (such as transient metals) due to presence of histidine, glutamic acid, aspartic acid, and phosphorylated serine and threonine residues Tong et al 2000); thus protecting oil against oxidation. Ma et al (2012) reported improved oxidative stability of flaxseed oil emulsions encapsulated by sodium caseinate cross-linked by transglutaminase during 30 days of storage. Kuhn and Cunha (2012) reported a significant increase in PV from 0 to 1.777 meq peroxides/kg oil of flaxseed oil emulsion homogenized at 80 MPa.…”
Section: Physical Stabilitymentioning
confidence: 99%
“…Hence, we suggest that the electrochemical method is a more potential technique than Tikekar's method which, however, has the advantage that it can be applied also for oil-water interfaces. Furthermore, this indicates that oxygen transfer may not be the explaining factor for improved oxidative stability of an emulsion with modified interfacial layer as demonstrated in our recent work [14].…”
Section: Better Performance Of Spray-dried Powder Via Interfacial Engsupporting
confidence: 48%
“…Enzymatic cross‐linking of interfacial casein after emulsification increased the cohesiveness of the interfacial layer of a casein‐stabilized O/W emulsion, but did not improve the oxidative stability of the emulsion (Kellerby and others ). More recently, protein enzymatic cross‐linking was performed prior to emulsification (Ma and others ). This appreciably improved both the physical stability of the emulsion and the oxidative stability of the lipid phase.…”
Section: Interfacial Properties Affecting Lipid Oxidation In Emulsionsmentioning
confidence: 99%